Cardiac Myxoma Presenting as Dyspnea after Cesarean Delivery - Allison Wyman; William Hurd; Justin Lappen (Case Reports in Medicine)
Introduction. Dyspnea during pregnancy and in the immediate postpartum or postoperative period is a relatively common symptom that can be an early sign of a life threatening condition. The differential diagnosis is broad and can represent a wide variety of underlying etiologies. Cardiac tumors are one of the rarest causes of dyspnea in a reproductive age women during the postpartum period. Case Presentation. 42-years old G7P1051 presented with acute dyspnea postoperatively after an elected uncomplicated repeat cesarean section and tubal ligation. The patient was diagnosed with a large left atrial cardiac myxoma and required urgent cardiothoracic surgery. Conclusion. The following case illustrates how a standard response to a common postpartum symptom, dyspnea, can divert and distract from less common exam findings. A careful, stepwise evaluation of symptoms and related findings will usually determine the underlying cause so that appropriate and timely treatment can be initiated.